Loss of allelic heterozygosity at a second locus on chromosome 11 in sporadic Wilms' tumor cells. - Reeve, A E (1989)
Children with associated Wilms' tumor, aniridia, genitourinary malformations, and mental retardation (WAGR syndrome) frequently have a cytogenetically visible germ line deletion of chromosomal band 11p13. In accordance with the Knudson hypothesis of two-hit carcinogenesis, the absence of this chromosomal band suggests that loss of both alleles of a gene at 11p13 causes Wilms' tumor. Consistent with this model, chromosomes from sporadically occurring Wilms' tumor cells frequently show loss of allelic heterozygosity at polymorphic 11p15 loci, and therefore it has been assumed that allelic loss extends proximally to include 11p13. We report here that in samples from five sporadic Wilms' tumors, allelic loss occurred distal to the WAGR locus on 11p13. In cells from one tumor, mitotic recombination occurred distal to the gamma-globin gene on 11p15.5. Thus, allelic loss in sporadic Wilms' tumor cells may involve a second locus on 11p.